The Efficacy of In-Phase and Quadrature Demodulation in Electronic Fetal Heart Rate Monitoring During Labor. Issue 2 (23rd April 2022) - Liang, Yiheng; Liu, Ping; Yan, Shaomei; Li, Yun; Chen, Duijin; Fan, Shangrong
Abstract: Objective: To investigate the efficacy of in-phase and quadrature (IQ) demodulation in electronic fetal heart rate monitoring (EFM) to reduce false reports of fetal heart rate (FHR) doubling or halving. Methods: This is a prospective cohort study. A total of 263 full-term pregnant women who delivered at Peking University Shenzhen Hospital between August 2019 and July 2020 were prospectively enrolled in the study. FHR monitoring began when the cervix was dilated to 2–3 cm and continued until delivery. Raw fetal Doppler audio signals and internal and external cardiotocography curves from internal electrode monitoring, EFM with conventional demodulation (external), and EFM with IQ demodulation (external) were acquired to compare FHR doubling and halving time. In cohort 1, FHR was compared between IQ demodulation and conventional demodulation. In cohort 2, FHR was compared between IQ demodulation, conventional demodulation, and internal FHR monitoring. Count data were statistically analyzed using the Chi-squared test, and measurement data were statistically analyzed using t -test for correlation coefficients, and Bland-Altman analysis for concordance ranges. Results: To compare IQ demodulation and conventional demodulation, 225 pregnant women were monitored for a total of 835, 870 seconds. The beat-to-beat interval of FHRs in raw fetal Doppler audio signals was used as the reference. The results showed a doubling time of 3401 seconds (0.407%, 3401/835, 870) and a halving time of 2918 seconds (0.349%, 2918/835, 870) with conventional demodulation, compared to 241 seconds (0.029%, 241/835, 870) and 589 seconds (0.070%, 589/835, 870), respectively, with IQ demodulation. IQ demodulation reduced FHR doubling by approximately 93% (3160/3401) and FHR halving by approximately 80% (2329/2918) compared to conventional demodulation ( P < 0.01). To compare IQ demodulation, conventional demodulation, and internal FHR monitoring, 38 pregnant women were monitored for a total of 98, 561 seconds. FHR from internal electrode monitoring was used as the reference. The results showed a doubling time of 238 seconds (0.241%, 238/98, 561) and a halving time of 235 seconds 0.238%, 235/98, 561) with conventional demodulation, compared with 30 seconds (0.030%, 30/98, 561) and 81 seconds (0.082%, 81/98, 561), respectively, with IQ demodulation ( P < 0.05). No significant difference was observed in doubling or halving time between IQ demodulation and internal FHR monitoring ( P > 0.05). IQ demodulation was more closely correlated with internal FHR monitoring than conventional demodulation (0.986 vs. 0.947). The Bland-Altman analysis showed that the concordance range of IQ demodulation vs. internal FHR monitoring was significantly narrower than that of conventional demodulation vs. internal FHR monitoring ((−5.32, 6.01) vs. (−10.87, 11.46)). Conclusion: EFM with IQ demodulation significantly reduces false FHR doubling and halving, with an efficacy similar to that of internal FHR monitoring.